The influence of E-WOM and Brand Image on Purchase Decisions for Games on the Steam Platform - Valentino Chandra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The phenomenon of Electronic Word of Mouth (E-WOM) in digital communities has become a dominant factor that can influence consumer behaviour, including purchasing decisions for games on digital distribution platforms such as Steam. The brand image formed from online interactions and consumer perceptions also plays an important role in shaping purchasing preferences. This research aims to explore how E-WOM and brand image influence purchasing decisions for digital games through a qualitative approach. The method used is a phenomenological study, with data collection techniques involving in-depth interviews with 12 active respondents who are users of the Steam platform and have purchased games based on recommendations or brand image. Data were analysed using a thematic approach to identify patterns of meaning and consumer experiences The research results indicate that E-WOM has a strong influence as a trusted source of information within the gaming community, particularly through forums, user reviews, and content creators. As for brand image, it fundamentally contributes to building emotional associations and quality perceptions towards certain games. These findings suggest that purchase decisions are driven not only by rational factors but also by affective ones shaped through digital social interactions.